2022
DOI: 10.3389/fimmu.2022.961405
|View full text |Cite
|
Sign up to set email alerts
|

The protective role of tissue-resident interleukin 17A–producing gamma delta T cells in Mycobacterium leprae infection

Abstract: Mycobacterium leprae is a kind of disease-causing bacteria and results in leprosy in human. Gamma delta (γδ) T cell is a T-cell subset that is presented in both human dermis and epidermis. These cells bridge innate and adaptive immune responses and play critical roles in regulating anti-microbial defense, wound healing, and skin inflammation. Here, we investigated skin resident γδ T cells in patients with leprosy. Our data showed that γδ T cells significantly accumulated in skin lesions of leprosy patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…We observed a significantly higher frequency of NKT-like cells and NK cells in the blood circulation of the T1R group when compared to the NR group of leprosy patients. A recent report demonstrated a significant accumulation of γδT cells within the skin lesions of the tuberculoid (TT) group of leprosy patients [ 31 ]. However, we observed the frequency of γδ T cells in blood circulation was found to be lower in T1R in comparison to the NR group.…”
Section: Discussionmentioning
confidence: 99%
“…We observed a significantly higher frequency of NKT-like cells and NK cells in the blood circulation of the T1R group when compared to the NR group of leprosy patients. A recent report demonstrated a significant accumulation of γδT cells within the skin lesions of the tuberculoid (TT) group of leprosy patients [ 31 ]. However, we observed the frequency of γδ T cells in blood circulation was found to be lower in T1R in comparison to the NR group.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that the main source of IL-17A production in the skin was IL-23 sensitive dermal γδ T cells, which could be a potential target for the therapy of leprosy. 77 …”
Section: How Leptin Modulates the Divergence Of CMI Response In Tuber...mentioning
confidence: 99%
“…They also found that the main source of IL-17A production in the skin was IL-23 sensitive dermal γδ T cells, which could be a potential target for the therapy of leprosy. 77 A study reported high a level of γδ T cells in LL patients. 78,79 The proportion of immunosuppressive CD4+TCR+FoxP3+ cells was shown to be the highest in LL patients when compared to that of TT patients and healthy controls.…”
Section: Other Smaller Subsets Of Lymphocytes Which Play Critical Rol...mentioning
confidence: 99%